2019
DOI: 10.22159/ajpcr.2018.v12i1.29489
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Antibiotic Used in Suspected Early-Onset Neonatal Sepsis From Malaysian Perspective: Which Ones to Choose and How Long to Give?

Abstract: Objective: Suspected early-onset sepsis is a common diagnosis among neonates which warrants admission to the neonatal intensive care unit. Prolonged empiric antibiotic is the biggest concern and treatment duration is still controversial. Antimicrobial stewardship (AMS) program promotes early antibiotic de-escalation to reduce unnecessary antibiotic exposure and its implementation in the intensive care setting seems to be feasible. The primary objective of this review was to compare the existing guidelines and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…The long-term microbiota effect of ABs and its associated negative health outcomes reinforce the need for implementing AB stewardship programs53–55 to avoid AB overuse 21 56 57. The microbiota perturbations were only significant after 5–7 days compared with 2–3 days AB which could explain previous findings from the INCA cohort: namely higher incidence of infantile colic, wheezing and food allergies in infants exposed for 5–7 days, but not for 2–3 days 10 58.…”
Section: Discussionmentioning
confidence: 83%
“…The long-term microbiota effect of ABs and its associated negative health outcomes reinforce the need for implementing AB stewardship programs53–55 to avoid AB overuse 21 56 57. The microbiota perturbations were only significant after 5–7 days compared with 2–3 days AB which could explain previous findings from the INCA cohort: namely higher incidence of infantile colic, wheezing and food allergies in infants exposed for 5–7 days, but not for 2–3 days 10 58.…”
Section: Discussionmentioning
confidence: 83%
“…2 shows the PAMAM dendrimers of two generations (G2 and G3) with different positive charges were attached to the streptavidin core through biotin click chemistry [100]. The study successfully demonstrated the improved ability of the protein molecule to cross the BBB by transcytosis via the endosomal pathway with high biocompatibility proving a new flexible nanoplatforms for the delivery of biopharmaceuticals can be hopefully developed [102].…”
Section: For Protein and Peptide Deliverymentioning
confidence: 95%